Value Added Intellectual Coefficient on Banks Performance in Indonesia - Salmiyah Thaha; Syarifuddin Sulaiman (Quantitative Economics and Management Studies, 2022)
Banks in Indonesia, both state-owned and private, have realized the importance of intellectual capital as a substantial part in achieving sustainable bank business growth. The population of this research is banking in Indonesia which consistently publish its financial position on an annual basis. Determination of the sample is carried out with a purposive approach, the sample of this research is banks that are listed on the Indonesia Stock Exchange and publish annual financial statements for the period 2018 - 2021. The analysis technique in this study uses simple linear regression analysis. The results show that each model from 2018-2021 shows a low value. The implication of this research is that the better the VAIC value, the more efficient the value creation of all resources will be.